2018
DOI: 10.1016/j.ebiom.2018.09.042
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic effect of Nutlin-3 combined with MG-132 on schwannoma cells through restoration of merlin and p53 tumour suppressors

Abstract: BackgroundThe great majority of sporadic vestibular schwannomas (VSs) are due to the mutations of the NF2 gene encoding merlin. Sporadic VSs exhibit variable growth patterns and only a small fraction of the tumours are fast-growing; however, the underlying mechanisms remain undefined.MethodsDNA sequencing and dosage analysis were used to identify the NF2 mutation status in sporadic schwannomas. The expression and sub-cellular localization of merlin and p53-MDM2 were assessed by immunoblotting, qRT-PCR and immu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 43 publications
(44 reference statements)
0
15
0
Order By: Relevance
“…The effect of MG-132 (one of the early proteasome inhibitors) and nutlin-3 on schwannoma cells has been assessed by Chen and colleagues. They have demonstrated that the differences in the expression of merlin, which is a tumor suppressor protein, in cancer cultures explain the functional diversity in response to nutlin-3 treatment [98]. It has been proved that dual therapy of nutlin-3 /MG-132 narrows the differences in the sensitivity to nutlin-3 in schwannoma cells.…”
Section: Drug Combinations For the Supporting Of Anti-cancer Activmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of MG-132 (one of the early proteasome inhibitors) and nutlin-3 on schwannoma cells has been assessed by Chen and colleagues. They have demonstrated that the differences in the expression of merlin, which is a tumor suppressor protein, in cancer cultures explain the functional diversity in response to nutlin-3 treatment [98]. It has been proved that dual therapy of nutlin-3 /MG-132 narrows the differences in the sensitivity to nutlin-3 in schwannoma cells.…”
Section: Drug Combinations For the Supporting Of Anti-cancer Activmentioning
confidence: 99%
“…It has been proved that dual therapy of nutlin-3 /MG-132 narrows the differences in the sensitivity to nutlin-3 in schwannoma cells. In addition, in vivo experiment with human xenograft model of schwannoma has revealed that the small-molecules work together to impose apoptosis [98].…”
Section: Drug Combinations For the Supporting Of Anti-cancer Activmentioning
confidence: 99%
“…Weak or non-bands were found in 'two-hit' tumors, showing that the inactivation of both alleles is necessary for the total loss of merlin expression. At least one somatic mutation occurred in more than 85% of the sporadic VS cases that affected the function of the NF2 gene [33].…”
Section: Pathophysiology Of Sporadic Formmentioning
confidence: 99%
“…The term "hit" means a DNA mutation in a cell [32]. The "two-hit" inactivation of NF2 leads to the loss of merlin [33]. This theory also involves the loss of chromosome 22 and biallelic genetic alterations of the NF2 gene are seen in the majority of the sporadic VS cases [26].…”
mentioning
confidence: 99%
See 1 more Smart Citation